Shape and size effects of ZnO nanocrystals on photocatalytic activity. - McLaren, A; Valdes-Solis, T; Li, G; Tsang, S (2009)
A wet-chemical method was employed to prepare zinc oxide nanocrystals having controlled morphology through thermal decomposition of a zinc precursor in self-assembled supramolecular structures in solvent under mild conditions. This solution method offers finer tailoring of the size and shape of the nanocrystals and is complementary to most reported physical methods. Understanding the morphological effects of pure or modified zinc oxide nanocrystals on photocatalytic activity is important in regard to enhanced solar energy capture and utilization but has been scarcely addressed in the past. The photocatalytic rate was found to have no dependence on ZnO particle size, but the shape factor seems to be of overriding importance. Hexagonal platelike nanocrystals were found to display at least 5 times higher activity than rod-shaped crystals, which clearly suggests that the polar (001) and (001) faces are more active surfaces than the nonpolar surfaces perpendicular to them.